Economic and Environmental Effectiveness of a Technology-based Climate Protocol - Carlo Carraro; Barbara Buchner (Fondazione Eni Enrico Mattei (FEEM), 2004)
The present stalemate in climate negotiations has led policy analysts and economists to explore the possible emergence of alternative climate regimes. This paper explores the idea of replacing international cooperation on greenhouse gas emission control with international cooperation on climate-related technological innovation and diffusion. This idea recently proposed among others by Barrett (2001) and Benedick (2001) is based on the insight that incentives to free-ride are much smaller in the case of technological cooperation than in the case of cooperation on emission control. This paper provides a first applied game theory analysis of a technology-based climate protocol by assessing: (i) the self-enforcingness (namely, the absence of incentives to free ride) of the coalition that would form when countries negotiate on climate-related technological cooperation; (ii) the environmental effectiveness of a technology-based climate protocol. The analysis is carried out by using a model in which endogenous and induced technical change are explicitly modelled and in which international technological spillovers are also quantified. The results of our analysis partly support Barrett's and Benedick's conjecture. On the one hand, a self-enforcing agreement is more likely to emerge when countries cooperate on environmental technological innovation and diffusion than when they cooperate on emission abatement. However, technological cooperation without any commitment to emission control may not lead to a sufficient abatement of greenhouse gas concentrations.
Keywords: C7; H0; H4; O3; 330; Agreements; Climate; Incentives; Technological change; Policy; Internationale Umweltpolitik; Klimaschutz; Umweltabkommen; Spieltheorie